Secondary battery and electric device

By introducing specific elements in the introduction of sulfide solid -state electrolytes to form covalent bonds, and modifying fluoride coating on the surface of lithium metal surface, the problem of unstable and lithium metal reactions in the air in the air in the air, which has been solved. The cycle performance and energy density of the battery.

CN119381516AActive Publication Date: 2025-01-28ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411587402.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-28
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The sulfide solid electrolyte is unstable in the air, and will react with water and degrade. Reaction with lithium metal can easily lead to a short circuit in the battery, limiting the increase in the battery's energy density.

Method used

By introducing AL, GA, IN, TI, SC, SB, SB, BI, V, NB and other elements in the introduction of sulfide solid-state electrolytes, P-O and SB-S/BI-S/In-S co-price bonds are formed to enhance the pair of pairs The resistance of the atmospheric degradation, and modify the fluoride of abillership on the lithium metal surface to form stable inorganic objects such as LIF to regulate the lithium nuclear and growth process.

Benefits of technology

It significantly improves the air stability of the solid electrolyte of sulfide, reduces the generation of H2S, and enhances the stability of lithium metal, thereby improving the cycle performance and energy density of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126795430000091
    Figure BDA0005126795430000091
Patent Text Reader

Abstract

The embodiment of the invention provides a secondary battery, the secondary battery comprises a positive electrode, a negative electrode and a sulfide solid electrolyte, the molecular formula of the sulfide solid electrolyte is LiaP1-bMbScOdXe, where, 5lt; a < lt >; 6, 0lt; blt; 1, 1.5 1t; clt; ct; 5, 0lt; dlt; 2.5, 4lt; c + dlt; 5, and 1lt; lt, lt; 2; m is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V and Nb; and X is selected from one or more of Cl, Br and I. The surface of the negative electrode comprises a fluoride silane coating. By designing the chemical structure of the sulfide solid electrolyte and applying a lithium metal surface modification technology, the problem that the sulfide solid electrolyte is unstable in air and the problem that the sulfide solid electrolyte reacts with lithium metal are solved, and the cycle performance of the lithium metal battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present application relate to the field of batteries, and in particular, to secondary batteries and electrical devices. Background Art

[0002] With the development of new energy fields, the performance of batteries has become increasingly important. In the field of batteries, the development of all-solid-state batteries is particularly important because all-solid-state batteries (ASSBs) using inorganic solid electrolytes (SEs) have higher safety and superior energy density compared to traditional lithium-ion batteries. For practical applications, sulfide solid electrolytes show a high energy density greater than 1 mS cm at room temperature (RT). -1 The high ionic conductivity and deformable mechanical properties of the sulfide solid electrolyte enable scalable cold stamping manufacturing, making it a promising candidate for solid electrolytes. However, the commonly used sulfide solid electrolytes are unstable in the air and will react with water to degrade. In addition, the sulfide solid electrolytes are unstable with lithium metal and will be reduced by lithium metal, which limits the negative electrode that matches the solid electrolyte, and thus limits the further improvement of the battery energy density. In addition, the current state of the technology also has the following disadvantages:

[0003] When the sulfide solid electrolyte is exposed to the air, problems such as the production of toxic gas H2S (hydrogen sulfide), complete destruction of the electrolyte structure, and degradation of electrochemical performance will occur. In addition, when matched with a lithium metal negative electrode, it will react chemically with the lithium metal, which can easily cause a short circuit in the battery. Summary of the invention

[0004] This application designs the chemical structure of the sulfide solid electrolyte and uses lithium metal surface modification technology to solve the problem of instability of the sulfide solid electrolyte in the air and the problem of reaction with lithium metal, thereby improving the cycle performance of the lithium metal battery.

[0005] Some embodiments of the present application provide a secondary battery, the secondary battery comprising: a positive electrode, a negative electrode and a sulfide solid electrolyte, wherein the molecular formula of the sulfide solid electrolyte is:

[0006] Li a P 1-b M b S c O d X e ,

[0007] Among them, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, and 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb; and X is selected from one or more of Cl, Br, I. The surface of the negative electrode includes a fluorinated silane coating. In some preferred embodiments, M is Sb, In, or Bi, and in some embodiments, X is Cl.

[0008] In the present application, by introducing one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb and O element into the sulfide solid electrolyte rich in halogen elements, P-O and Sb-S / Bi-S / In-S / Al-S / Ga covalent bonds are formed in the crystal structure of the sulfide solid electrolyte, thereby increasing the inherent resistance to atmospheric degradation and effectively reducing the generation of H2S, thus enhancing the air stability of the sulfide solid electrolyte.

[0009] In addition, the negative electrode includes lithium metal. By modifying the surface of the lithium metal of the negative electrode with a fluorinated silane coating, stable inorganic substances such as LiF (lithium fluoride) can be formed in-situ, homogenize the electric field, balance the local current density, and thus regulate the nucleation and growth process of Li. In addition, LiF has a high interfacial energy, which can partially alleviate the rapid growth of lithium dendrites at the interface.

[0010] In some embodiments, 0 < b < 0.1. In a further embodiment, when the valence of M is +5, b is 0.04, and when the valence of M is +3, b is 0.02. This is because too much doping of M element will cause changes in the crystal structure of the sulfide, thus affecting the conductivity stability, etc. Therefore, when b is 0.04 or 0.02, the performance is the most balanced.

[0011] In some embodiments, the fluorinated silane coating is a triethyl(trifluoromethyl)silane coating. In the present application, due to the low surface energy of triethyl(trifluoromethyl)silane, it can quickly spread on the surface of lithium metal. Fluorinated silanes such as triethyl(trifluoromethyl)silane can react with lithium metal to generate LiF, which can accelerate the lithium ion transport kinetics, promote the uniform deposition of lithium on the surface of lithium metal, and inhibit the growth of lithium dendrites.

[0012] In some embodiments, the thickness of the triethyl (trifluoromethyl) silane coating is 1 μm-10 μm, such as its corresponding volume is 10 μL-100 μL. In some embodiments, when the thickness of the triethyl (trifluoromethyl) silane coating is 1 μm-10 μm, such as its corresponding volume is in the range of 10 μL-100 μL, the triethyl (trifluoromethyl) silane coating can generate an SEI film in situ with lithium metal, and the capacity is very high, and the battery cycle stability is good. In some embodiments, the thickness of the triethyl (trifluoromethyl) silane coating is 6 μm, such as its corresponding volume is 60 μL. When the thickness of the triethyl (trifluoromethyl) silane coating is 6 μm, it can generate a stable and moderately thick SEI film in situ with lithium metal, and the battery performance is the best and most balanced.

[0013] Some embodiments of the present application also provide an electrical device including the secondary battery.

[0014] In the present application, by introducing one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb and O element into the sulfide solid electrolyte, PO and Sb-S / Bi-S / In-S... bonds are formed in the crystal structure of the sulfide solid electrolyte, thereby increasing the intrinsic resistance to atmospheric degradation and effectively reducing the generation of H2S, thereby enhancing the air stability of the sulfide solid electrolyte.

[0015] In addition, by modifying the fluorinated silane coating on the lithium metal surface of the negative electrode, stable inorganic substances such as LiF (lithium fluoride) can be formed in situ to homogenize the electric field and balance the local current density, thereby regulating the nucleation and growth process of Li. In addition, LiF has a high interfacial energy, which can partially alleviate the rapid growth of lithium dendrites at the interface. DETAILED DESCRIPTION

[0016] The secondary battery provided in the present application adopts a two-pronged approach. A sulfide solid electrolyte that is stable with air and metallic lithium at the negative electrode is designed through a chemical structure. At the same time, a fluorinated silane coating is modified on the surface of the lithium metal at the negative electrode to improve the stability between the lithium metal and the sulfide solid electrolyte, thereby solving the problem of the sulfide solid electrolyte being unstable in air and the problem of reacting with the lithium metal at the negative electrode, thereby improving the cycle performance of the secondary battery.

[0017] Specifically, some embodiments of the present application provide a secondary battery, which includes: a positive electrode, a negative electrode, and a sulfide solid electrolyte, and the molecular formula of the sulfide solid electrolyte is:

[0018] Li a P 1-b M b S c O d Xe ,

[0019] Among them, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, and 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb; and X is selected from one or more of Cl, Br, I. The surface of the negative electrode includes a fluorinated silane coating.

[0020] In the present application, by introducing one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb and O element into the sulfide solid electrolyte rich in halogen elements, P-O and Sb-S / Bi-S / In-S / Al-S / Ga... bonds are formed in the crystal structure of the sulfide solid electrolyte, thereby increasing the inherent resistance to atmospheric degradation and effectively reducing the generation of H2S, thus enhancing the air stability of the sulfide solid electrolyte.

[0021] In addition, the negative electrode includes lithium metal. By modifying the surface of the lithium metal of the negative electrode with a fluorinated silane coating, stable inorganic substances such as LiF (lithium fluoride) can be formed in-situ, homogenize the electric field, balance the local current density, and thus regulate the nucleation and growth process of Li. In addition, LiF has a relatively high interfacial energy, which can partially alleviate the rapid growth of lithium dendrites at the interface.

[0022] In some embodiments, M is Sb, In or Bi. In some embodiments, X is Cl. In the present application, when X is Cl, a chlorine-rich sulfide solid electrolyte is formed. And by introducing Sb / Bi / In and O element into the chlorine-rich sulfide solid electrolyte, P-O and Sb-S / Bi-S / In-S bonds are formed in the crystal structure of the sulfide solid electrolyte, thereby increasing the inherent resistance to atmospheric degradation and effectively reducing the generation of H2S, thus enhancing the air stability of the sulfide solid electrolyte.

[0023] In some embodiments, 0 < b < 0.1. In a further embodiment, when the valence of M is +5, b is 0.04, and when the valence of M is +3, b is 0.02. This is because too much doping of M element will cause changes in the crystal structure of the sulfide, thus affecting the conductivity stability, etc. Therefore, when b is 0.04 or 0.02, the performance is the most balanced.

[0024] In some embodiments, the fluorinated silane coating is a triethyl (trifluoromethyl) silane coating. In the present application, due to the low surface energy of triethyl (trifluoromethyl) silane, it can be quickly spread on the surface of lithium metal. Fluorinated silanes such as triethyl (trifluoromethyl) silane can react with lithium metal to generate LiF, which can accelerate the lithium ion transfer kinetics, promote the uniform deposition of lithium on the surface of lithium metal, and inhibit the growth of lithium dendrites.

[0025] In some embodiments, the thickness of the triethyl (trifluoromethyl) silane coating is 1 μm-10 μm, and in some cases, it corresponds to 10 μL-100 μL. In some embodiments, when the thickness of the triethyl (trifluoromethyl) silane coating is in the range of 1 μm-10 μm, the triethyl (trifluoromethyl) silane coating can generate an SEI film in situ with lithium metal, and the capacity is very high, and the battery cycle stability is good. In some embodiments, the thickness of the triethyl (trifluoromethyl) silane coating is 6 μm, and in some cases, it corresponds to 60 μL. When the thickness of the triethyl (trifluoromethyl) silane coating is 6 μm, it can generate a stable and moderately thick SEI film in situ with lithium metal, and the battery performance is the best and most balanced.

[0026] Some embodiments of the present application also provide an electrical device including the secondary battery.

[0027] In the present application, the secondary battery includes a positive electrode, a negative electrode and a sulfide solid electrolyte, and the relevant preparation method is as follows.

[0028] The positive electrode active material, positive electrode conductive agent, and positive electrode binder are dispersed in a solvent in a mass ratio of 95:2:3 to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the surface of the positive electrode current collector. After drying, cold pressing and other processes, a positive electrode active material layer is formed on the positive electrode current collector, thereby serving as the positive electrode in the present technical solution. The ratio between the components in the positive electrode slurry can be set with reference to the conventional ratio, and is not limited here. The positive electrode active material is a positive electrode active material coated on the positive electrode current collector as conventionally understood in the art. The type of the positive electrode active material may be one or more of lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA). The positive electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The positive electrode binder is selected from one of PVDF and its derivatives. In some embodiments, the positive electrode current collector may be aluminum foil.

[0029] Drop 10 - 100 μL of triethyl(trifluoromethyl)silane on the polished lithium metal surface. The thickness of the formed triethyl(trifluoromethyl)silane is 1 μm - 10 μm, thereby forming a lithium metal (such as lithium metal with a thickness of ≤0.6 mm, and common lithium metals are all applicable) with a fluorosilane coating on the surface, which is used as the negative electrode in this technical solution.

[0030] The preparation method of the sulfide solid electrolyte in this application includes the following steps:

[0031] 1) According to the chemical formula Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, and 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb; and X is selected from one or more of Cl, Br, I. After mixing the raw materials evenly according to the stoichiometry, place them in a ball mill jar and ball mill for 24 h, where the ball mill rotation speed is 600 rpm and the ball-to-material ratio is 40:1 to obtain a sulfide solid electrolyte precursor powder. Among them, the above raw materials include Li2S, LiX, P2S5, and the oxide MxOy corresponding to the M element. X is selected from one or more of Cl, Br, or I, and M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb. Its stoichiometric ratio is determined according to the molar ratio of each element in Li a P 1-b M b S c O d X e ;

[0032] 2) Anneal the precursor powder at 500 °C for 24 h to obtain a sulfide solid electrolyte.

[0033] Finally, place the positive electrode, sulfide solid electrolyte, and negative electrode into the mold for assembly in sequence; after assembly, apply pressure and tighten the nut at the top of the column with a constant pressure, and then a secondary battery is obtained. The assembly process is completed in a glove box under an argon atmosphere.

[0034] Those skilled in the art will understand that the above-described preparation method of the battery is only an example. Other commonly used methods in the art can be adopted without departing from the content disclosed in this application.

[0035] The reagents and raw materials used in the present invention are all commercially available.

[0036] The present invention has no special requirements for the assembly method of the above-mentioned battery, and an assembly method familiar to those skilled in the art can be used. In addition, the above-mentioned technical solution can be applied not only to commonly used all-solid-state lithium-ion batteries, but also to all-solid-state sodium-ion batteries, all-solid-state potassium-ion batteries and other types of kinetic batteries. The above-mentioned secondary battery can be applied to any suitable electrical device, including but not limited to electric vehicles.

[0037] Some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0038] Example 1

[0039] Preparation of sulfide solid electrolyte:

[0040] The raw materials Li2S, LiCl, P2S5 and In2O3 were mixed evenly according to the stoichiometric ratio of 1.5:2:0.49:0.01, and then placed in a ball mill for 24 hours. The ball mill speed was 600rpm, and the ball-to-material ratio was 40:1. After the ball milling was completed, the sulfide solid electrolyte precursor powder was obtained. Then the precursor powder was annealed and sintered at a high temperature of 500℃ for 24 hours to obtain the sulfide solid electrolyte Li 5.5 P 0.98 In 0.02 S 4.45 O 0.03 Cl 1.5 .

[0041] Preparation of lithium metal pole piece:

[0042] 60 μL of triethyl (trifluoromethyl) silane was dropped onto the polished lithium metal surface to form a lithium metal with a surface modified with a 6 μm thick fluorinated silane coating as a negative electrode, wherein the fluorinated silane was triethyl (trifluoromethyl) silane.

[0043] The sulfide solid electrolyte and lithium metal pole piece prepared by the above method were further assembled into lithium-lithium symmetric batteries and full batteries for cycle and discharge retention performance tests.

[0044] Example 2

[0045] The preparation method is consistent with that of Example 1, except that in Example 2, 10 μL of triethyl (trifluoromethyl) silane is added dropwise to the polished lithium metal surface, and the thickness of the formed triethyl (trifluoromethyl) silane coating is 1 μm.

[0046] Example 3

[0047] The preparation method is consistent with that of Example 1, except that in Example 3, 100 μL of triethyl (trifluoromethyl) silane is added dropwise to the polished lithium metal surface, and the thickness of the formed triethyl (trifluoromethyl) silane coating is 10 μm.

[0048] Example 4

[0049] The preparation method is consistent with that of Example 1, except that in Example 4, 30 μL of triethyl (trifluoromethyl) silane is added dropwise to the polished lithium metal surface, and the thickness of the formed triethyl (trifluoromethyl) silane coating is 3 μm.

[0050] Example 5

[0051] The preparation method is consistent with that of Example 1, except that in Example 5, 80 μL of triethyl (trifluoromethyl) silane is added dropwise to the polished lithium metal surface, and the thickness of the formed triethyl (trifluoromethyl) silane coating is 8 μm.

[0052] Example 6

[0053] The preparation method is consistent with that of Example 1, except that the sulfide solid electrolyte in Example 6 adopts Li 5.5 P 0.98 Sb 0.02 S 4.45 O 0.03 Cl 1.5 .

[0054] Example 7

[0055] The preparation method is consistent with that of Example 1, except that the sulfide solid electrolyte in Example 7 uses Li 5.5 P 0.98 Bi 0.02 S 4.45 O 0.03 Cl 1.5 .

[0056] Example 8

[0057] The preparation method is consistent with that of Example 1, except that the sulfide solid electrolyte in Example 8 uses Li 5.5 P 0.96 V 0.04 S 4.4 O 0.1 Cl 1.5 .

[0058] Comparative Example 1

[0059] The preparation method is consistent with that in Example 1, except that in Comparative Example 1, 1 μL of triethyl (trifluoromethyl) silane is dripped onto the polished lithium metal surface, and the thickness of the formed triethyl (trifluoromethyl) silane coating is 0.1 μm.

[0060] Comparative Example 2

[0061] The preparation method is consistent with that in Example 1, except that in Comparative Example 2, 200 μL of triethyl (trifluoromethyl) silane is dripped onto the polished lithium metal surface, and the thickness of the formed triethyl (trifluoromethyl) silane coating is 20 μm.

[0062] Comparative Example 3

[0063] The preparation method is consistent with that of Example 1, except that in Comparative Example 3, no fluorinated silane coating is modified on the surface of the lithium metal.

[0064] Comparative Example 4

[0065] The preparation method is consistent with that in Example 1, except that the sulfide solid electrolyte in Comparative Example 4 uses Li6PS5Cl, and no fluorinated silane coating is modified on the surface of the lithium metal.

[0066] Performance Testing Methods

[0067] Lithium-Lithium Symmetric Battery Test: Li prepared in Examples 1-8 above 5.5 P 0.98 In 0.02 S 4.45 O 0.03 Cl 1.5 / Li 5.5 P 0.98 Sb 0.02 S 4.45 O 0.03 Cl 1.5 / Li 5.5 P 0.98 Bi 0.02 S 4.45 O 0.03 Cl 1.5 / Li 5.5 P 0.96 V 0.04 S 4.4 O 0.1 Cl 1.5 As electrolyte, lithium metal sheet modified with fluorinated silane was used as lithium metal symmetric electrode. The symmetric battery prepared above was charged and discharged for a long cycle at 25°C, and the charge and discharge rate was measured to be 0.5 mA / cm 2 , and the charging and discharging time is 1h.

[0068] Full battery test: LiNi 0.8 Co 0.1 Mn 0.1 O2 as the positive electrode, lithium metal modified with silane fluoride as the negative electrode, and the Li prepared in Examples 1-8 above 5.5 P0.98 In 0.02 S 4.45 O 0.03 Cl 1.5 / Li 5.5 P 0.98 Sb 0.02 S 4.45 O 0.03 Cl 1.5 / Li 5.5 P 0.98 Bi 0.02 S 4.45 O 0.03 Cl 1.5 / Li 5.5 P 0.96 V 0.04 S 4.4 O 0.1 Cl 1.5 The electrolyte was used. The full battery prepared above was charged and discharged for a long cycle at 25°C, and the capacity retention rate at a charge and discharge rate of 1C / 1C was measured. The specific preparation method of the positive and negative electrodes of the full battery is as follows.

[0069] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, positive electrode conductive agent Super P, positive electrode binder polyvinylidene fluoride and corresponding sulfide electrolyte are mixed and dispersed in xylene according to a mass ratio of 75:1:1:23, and stirred to a uniform state under the action of a vacuum mixer to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on aluminum foil, and the aluminum foil is dried at room temperature and transferred to the vacuum transition chamber of the glove box for drying, and then cold pressed and cut to obtain the positive electrode.

[0070] A polyethylene (PE) porous polymer film is used as the separator.

[0071] Finally, the positive electrode, the separator, the lithium metal negative electrode and the sulfide solid electrolyte prepared in each embodiment and comparative example are placed into the mold for assembly in turn. After assembly, pressurize and tighten the nut on the top of the column to a constant pressure to obtain a full battery.

[0072] The test results are shown in Table 1 below.

[0073] Table 1. Secondary battery performance test results of Examples 1 to 18 and Comparative Examples 1 to 12

[0074]

[0075] By comparing the above examples 1-8 with comparative examples 3-4, it can be seen that the secondary battery provided by the present application is provided by using a halogen-rich sulfide solid electrolyte (Li a P 1-bM b S c O d X e ) is introduced into the sulfide solid electrolyte, so that it forms PO and Sb-S / Bi-S / In-S / VS covalent bonds in the crystal structure of the sulfide solid electrolyte, thereby increasing the intrinsic resistance to atmospheric degradation and effectively reducing the generation of H2S, thereby enhancing the air stability of the sulfide solid electrolyte. In addition, by modifying the fluorinated silane coating on the lithium metal surface of the negative electrode, stable inorganic substances such as LiF (lithium fluoride) can be formed in situ, so that the electric field is uniform, and the local current density is balanced, thereby regulating the nucleation and growth process of Li. In addition, LiF has a higher interface energy, which can partially alleviate the rapid growth of lithium dendrites at the interface. As can be seen from Examples 1-8, the lithium-lithium symmetrical battery in the above Examples 1-8 has a large current density of 0.5mA / cm 2 Under the condition of 1000 hours of stable cycling, the full battery can be more than doubled compared with the full battery assembled with unmodified lithium metal in Comparative Examples 3-4. In addition, it can be seen from Comparative Examples 3-4 that according to the design of the chemical structure of the sulfide solid electrolyte itself in Comparative Example 3, compared with the ordinary sulfide in Comparative Example 4, for example, the battery capacity and cycle life of Li6PS5Cl will increase, but there will still be side reactions when matching with unmodified lithium metal, and it can be further seen from Comparative Example 4 that the side reactions of Li6PS5Cl and lithium metal are more intense, which reduces the cycle performance of the battery.

[0076] It can be seen from Examples 1-5 and Comparative Examples 1-2 that the thickness of the triethyl (trifluoromethyl) silane coating is 1 μm-10 μm, and its corresponding volume is 10 μL-100 μL. When the thickness of the triethyl (trifluoromethyl) silane coating is in the range of 1 μm-10 μm, the triethyl (trifluoromethyl) silane coating can generate an SEI film in situ with lithium metal, and the capacity is very high, and the battery cycle stability is good. In some embodiments, the thickness of the triethyl (trifluoromethyl) silane coating is 6 μm, and its corresponding volume is 60 μL. When the thickness of the triethyl (trifluoromethyl) silane coating is 6 μm, it can generate a stable and moderately thick SEI film in situ with lithium metal, and the battery performance is the best and most balanced. It can be seen from Examples 3 and 5 that when the volume of the triethyl (trifluoromethyl) silane coating is 100 μL and 80 μL, a large amount of SEI film will be generated in situ with lithium metal, and the battery cycle stability is good. It can be seen from Comparative Example 1 that when the triethyl (trifluoromethyl) silane coating is too little (e.g., 1 μL), it can hardly protect the lithium metal and the battery performance is poor. It can be seen from Comparative Example 5 that when the triethyl (trifluoromethyl) silane coating is too much (e.g., 200 μL), the battery capacity is greatly affected and the capacity is low.

[0077] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.

Claims

1. A secondary battery, characterized in that: Comprising: a positive electrode, a negative electrode, and a sulfide solid electrolyte, the molecular formula of the sulfide solid electrolyte being: Li a P 1-b M b S c O d X e , wherein 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, and 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb; and X is selected from one or more of Cl, Br, I, the surface of the negative electrode includes a fluorinated silane coating.

2. The secondary battery according to claim 1, characterized in that: The M is Sb, In, or Bi.

3. The secondary battery according to claim 1 or 2, characterized in that: The X is Cl.

4. The secondary battery according to claim 1, characterized in that: 0<b<0.1。 5. The secondary battery according to claim 4, characterized in that: The valence of M is +5, and b is 0.

04.

6. The secondary battery according to claim 4, characterized in that: The valence of M is +3, and b is 0.

02.

7. The secondary battery according to claim 1, characterized in that: The fluorinated silane coating is a triethyl(trifluoromethyl)silane coating.

8. The secondary battery according to claim 1, characterized in that: The thickness of the fluorinated silane coating is 1 μm - 10 μm.

9. The secondary battery according to claim 8, characterized in that: The thickness of the fluorinated silane coating is 6 μm.

10. An electrical device, characterized in that: Comprising a secondary battery according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of all-solid-state sulfide electrolyte for lithium ion battery

    CN112421119A

  • High-stability inorganic sulfide solid electrolyte and preparation method thereof

    CN113363569A

  • Hybrid functionalized fluoropolymers for lithium ion batteries

    CN114402467A

  • Lithium metal negative electrode and manufacturing method thereof

    CN116130609A

  • Solid electrolyte material, preparation method and solid-state battery

    CN117728010A